Degradable lunch box and production process thereof

By introducing bamboo powder, soy starch and composite modified fillers into the polylactic acid material, a degradable lunch box with improved mechanical properties was prepared, which solved the problem of insufficient impact strength of the existing polylactic acid lunch box, achieved higher heat resistance, impact resistance and toughness, and also significantly improved in terms of environmental friendliness.

CN119552487AActive Publication Date: 2025-03-04SHENZHEN HONGCAI NEW MATERIAL TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411934466.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing lunch boxes prepared by polylactic acid materials are relatively average in mechanical properties and relatively poor impact strength, which limit their application.

Method used

A biodegradable lunch box is prepared by combining bamboo powder, polylactic acid resin, stearate, composite modified filler and starch. Among them, the composite modified filler is prepared by mixing and refining the calcined bentonite, polybutylene succinate and coupling agent, improving the heat resistance and impact resistance of the material; soybean starch is denaturated to enhance the toughness of the material; bamboo powder improves the hardness and strength properties.

Benefits of technology

It improves the mechanical properties of the degradable lunch box, including heat resistance, impact resistance and toughness, making it more suitable for occasions where it withstands certain pressures and wear, and at the same time decomposes faster in the natural environment, reducing long-term pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552487A_ABST
    Figure CN119552487A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable lunch box and a production process thereof. The degradable lunch box is prepared from the following components: bamboo powder, polylactic resin, stearate, composite modified filler and starch. The degradable lunch box prepared by the invention belongs to an environment-friendly lunch box, can be subjected to biochemical reaction under the action of a natural environment and enzyme, and is finally degraded into carbon dioxide and water, so that the pollution to the environment is reduced. The main raw material is polylactic acid which is derived from renewable resources such as corn starch and the like and has good biodegradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of degradable materials, in particular to a degradable lunch box and a production process thereof. Background Art

[0002] With the rise of the fast food industry, the use of fast food packaging boxes is increasing. Due to the large-scale use of plastic lunch boxes, after they are discarded, white pollution will become increasingly serious, endangering the human living environment. Therefore, the development of degradable materials is in line with the needs of ecological development and has a huge market demand.

[0003] Degradable tableware refers to tableware that can undergo biochemical reactions under the action of microorganisms (bacteria, mold, algae) and enzymes in the natural environment, causing changes from mold in appearance to internal quality, and ultimately forming carbon dioxide and water.

[0004] In the prior art, lunch boxes are prepared by using polylactic acid materials. Since polylactic acid materials have excellent biodegradability, they have been widely used in the field of biodegradable materials. However, lunch boxes made from pure polylactic acid materials have relatively general mechanical properties, especially relatively poor impact strength, which limits their application.

[0005] Therefore, the present invention solves the corresponding problems by providing a degradable lunch box. Summary of the invention

[0006] The purpose of the present invention is to provide a degradable lunch box to solve the deficiencies in the prior art.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A degradable lunch box comprises the following ingredients by weight: 20-30 parts of bamboo powder, 60-75 parts of polylactic acid resin, 1-2 parts of stearate, 10-15 parts of composite modified filler and 12-16 parts of starch.

[0009] As a further technical solution: the preparation method of the composite modified filler is:

[0010] First, the bentonite is calcined to obtain calcined bentonite;

[0011] Add polybutylene succinate, calcined bentonite and coupling agent into a mixer in sequence, and mix and stir for 40 minutes to obtain a uniform mixture;

[0012] The uniform mixture obtained above is added into an internal mixer for internal mixing. After the internal mixing is completed, the mixture is discharged to obtain a composite modified filler.

[0013] As a further technical solution: the method for preparing calcined bentonite is:

[0014] The bentonite and nitric acid solution were mixed in a mass ratio of 1:5, heated to 80°C, stirred for 40 minutes, then centrifuged, filtered, washed to neutrality, and dried to obtain;

[0015] Wherein, the mass fraction of nitric acid solution is 5%;

[0016] The stirring speed is 300r / min;

[0017] The centrifugal speed was 8000 r / min and the centrifugal time was 15 min;

[0018] The drying temperature was 80°C and the drying time was 2 hours.

[0019] As a further technical solution: the mass ratio of the polybutylene succinate, calcined bentonite and coupling agent is 10-12:20-25:1-1.4;

[0020] The coupling agent is an organic silane coupling agent;

[0021] The organic silane coupling agent is vinyltrimethoxysilane.

[0022] As a further technical solution: the mixing process parameters are:

[0023] The mixing temperature is 180°C, the mixing speed is 75r / min, and the mixing time is 40-50min.

[0024] As a further technical solution: the stearate is calcium stearate.

[0025] As a further technical solution: the starch is soybean starch;

[0026] The soybean starch is subjected to modification treatment:

[0027] The soybean starch is added to the nitric acid solution, the temperature is adjusted to 90°C, the mixture is kept warm and stirred for 2 hours, then adjusted to neutrality, and dried to a moisture content of less than 5% to obtain;

[0028] The mixing ratio of the soybean starch and the nitric acid solution is 30 g:120 mL.

[0029] A production process for a degradable lunch box comprises the following steps:

[0030] (1) Preparation of materials: weighing bamboo powder, polylactic acid resin, stearate, composite modified filler, and starch according to respective weight parts;

[0031] (2) Mixing: Add each component to a high-speed mixer in sequence, mix the raw materials evenly, and obtain a mixed raw material;

[0032] (3) Banburying: adding the mixed raw materials into a banbury mixer for banburying and kneading to obtain a banburying rubber compound;

[0033] (4) Mixing: adding the mixed rubber material to an open mixer for mixing to obtain a mixed material;

[0034] (5) Molding: The mixed material is added to an extruder for plasticization, and then pressed into shape in a mold, and cooled to room temperature to obtain a degradable lunch box.

[0035] As a further technical solution: the mixing time in the high-speed mixer in step (2) is 40 minutes;

[0036] The temperature of the banburying in step (3) is 155° C. and the time is 25 min.

[0037] As a further technical solution: in step (4), the mixing temperature is 188°C and the mixing time is 30 min;

[0038] In step (5), the mold temperature is 135° C., the pressing pressure is 12 MPa, and the pressing time is 50 s.

[0039] Beneficial effects:

[0040] characteristic:

[0041] The degradable lunch box prepared by the invention is an environmentally friendly lunch box, which can undergo biochemical reactions under the action of a natural environment and enzymes and eventually degrade into carbon dioxide and water, thereby reducing pollution to the environment.

[0042] The main raw material of the invention is polylactic acid, which is derived from renewable resources such as corn starch and has good biodegradability.

[0043] Compared with traditional plastic lunch boxes, the degradable lunch boxes prepared by the present invention can decompose faster in the natural environment, reducing long-term pollution to the environment; they are made of non-toxic and harmless raw materials, meet national food hygiene standards, and are safer and more reliable to use; they can be made into various shapes and specifications according to different needs to meet the usage needs in different scenarios.

[0044] In order to improve the mechanical properties of the degradable lunch box prepared by the present invention, the present invention introduces the prepared composite modified filler to promote the crystallization of polylactic acid, thereby improving its heat resistance and impact resistance. At the same time, the treated bentonite can better combine with the matrix PLA resin, thereby increasing the heat deformation temperature of the degradable lunch box prepared by the present invention and improving the impact strength.

[0045] The soybean starch is subjected to a modification treatment and then forms an interpenetrating network structure or a eutectic structure with polylactic acid, thereby enhancing the toughness of the degradable lunch box prepared by the present invention.

[0046] By introducing bamboo powder and combining it with a composite modified filler, the hardness and strength of the degradable lunch box prepared by the present invention can be improved, making it more suitable for occasions that need to withstand certain pressure and wear.

[0047] The introduction of the treated soybean starch, combined with the effect of the modified composite filler, significantly improves the processing fluidity of the material, which is crucial for the processing and molding process of the degradable lunch box prepared by the present invention and helps to improve production efficiency and product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The present invention is a flow chart for preparing a degradable lunch box. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The following are specific embodiments

[0051] Example 1

[0052] A production process for a degradable lunch box comprises the following steps:

[0053] (1) Preparation of materials: Weigh the following materials in parts by weight: 20 parts of bamboo powder, 60 parts of polylactic acid resin, 1 part of stearate, 10 parts of composite modified filler, and 12 parts of starch.

[0054] The preparation method of the composite modified filler is as follows:

[0055] First, the bentonite is calcined to obtain calcined bentonite;

[0056] Add polybutylene succinate, calcined bentonite and coupling agent into a mixer in sequence, and mix and stir for 40 minutes to obtain a uniform mixture;

[0057] The uniform mixture obtained above is added into an internal mixer for internal mixing. After the internal mixing is completed, the mixture is discharged to obtain a composite modified filler.

[0058] The preparation method of calcined bentonite is:

[0059] The bentonite and nitric acid solution were mixed in a mass ratio of 1:5, heated to 80°C, stirred for 40 minutes, then centrifuged, filtered, washed to neutrality, and dried to obtain;

[0060] Wherein, the mass fraction of nitric acid solution is 5%;

[0061] The stirring speed is 300r / min;

[0062] The centrifugal speed was 8000 r / min and the centrifugal time was 15 min;

[0063] The drying temperature was 80°C and the drying time was 2 hours.

[0064] The mass ratio of polybutylene succinate, calcined bentonite and coupling agent is 10:20:1;

[0065] The coupling agent is an organic silane coupling agent;

[0066] The organic silane coupling agent is vinyltrimethoxysilane.

[0067] The mixing process parameters are:

[0068] The mixing temperature is 180°C, the mixing speed is 75r / min, and the mixing time is 40min.

[0069] The stearate is calcium stearate.

[0070] The starch is soybean starch;

[0071] The soybean starch is subjected to modification treatment:

[0072] The soybean starch is added to the nitric acid solution, the temperature is adjusted to 90°C, the mixture is kept warm and stirred for 2 hours, then adjusted to neutrality, and dried to a moisture content of less than 5% to obtain;

[0073] The mixing ratio of the soybean starch and the nitric acid solution is 30 g:120 mL.

[0074] (2) Mixing: Add each component to a high-speed mixer in sequence, mix the raw materials evenly, and obtain a mixed raw material; the mixing time in the high-speed mixer is 40 minutes;

[0075] (3) Internal mixing: the mixed raw materials are added into an internal mixer for internal mixing and kneading to obtain an internal mixing rubber material; the internal mixing temperature is 155°C and the time is 25 min.

[0076] (4) Mixing: adding the internal mixing rubber material to an open mixer for mixing to obtain a mixed material; the mixing temperature is 188° C. and the mixing time is 30 min;

[0077] (5) Molding: The mixed material is added to an extruder for plasticization, and then pressed into shape in a mold, and cooled to room temperature to obtain a degradable lunch box; the mold temperature is 135° C., the pressing pressure is 12 MPa, and the pressing time is 50 s.

[0078] Example 2

[0079] A production process for a degradable lunch box comprises the following steps:

[0080] (1) Preparation of materials: Weigh the following materials in parts by weight: 24 parts of bamboo powder, 66 parts of polylactic acid resin, 1.5 parts of stearate, 12 parts of composite modified filler, and 15 parts of starch.

[0081] The preparation method of the composite modified filler is as follows:

[0082] First, the bentonite is calcined to obtain calcined bentonite;

[0083] Add polybutylene succinate, calcined bentonite and coupling agent into a mixer in sequence, and mix and stir for 40 minutes to obtain a uniform mixture;

[0084] The uniform mixture obtained above is added into an internal mixer for internal mixing. After the internal mixing is completed, the mixture is discharged to obtain a composite modified filler.

[0085] The preparation method of calcined bentonite is:

[0086] The bentonite and nitric acid solution were mixed in a mass ratio of 1:5, heated to 80°C, stirred for 40 minutes, then centrifuged, filtered, washed to neutrality, and dried to obtain;

[0087] Wherein, the mass fraction of nitric acid solution is 5%;

[0088] The stirring speed is 300r / min;

[0089] The centrifugal speed was 8000 r / min and the centrifugal time was 15 min;

[0090] The drying temperature was 80°C and the drying time was 2 hours.

[0091] The mass ratio of polybutylene succinate, calcined bentonite and coupling agent is 11:20:1.2;

[0092] The coupling agent is an organic silane coupling agent;

[0093] The organic silane coupling agent is vinyltrimethoxysilane.

[0094] The mixing process parameters are:

[0095] The mixing temperature is 180°C, the mixing speed is 75r / min, and the mixing time is 45min.

[0096] The stearate is calcium stearate.

[0097] The starch is soybean starch;

[0098] The soybean starch is subjected to modification treatment:

[0099] The soybean starch is added to the nitric acid solution, the temperature is adjusted to 90°C, the mixture is kept warm and stirred for 2 hours, then adjusted to neutrality, and dried to a moisture content of less than 5% to obtain;

[0100] The mixing ratio of the soybean starch and the nitric acid solution is 30 g:120 mL.

[0101] (2) Mixing: Add each component to a high-speed mixer in sequence, mix the raw materials evenly, and obtain a mixed raw material; the mixing time in the high-speed mixer is 40 minutes;

[0102] (3) Internal mixing: the mixed raw materials are added into an internal mixer for internal mixing and kneading to obtain an internal mixing rubber material; the internal mixing temperature is 155°C and the time is 25 min.

[0103] (4) Mixing: adding the internal mixing rubber material to an open mixer for mixing to obtain a mixed material; the mixing temperature is 188° C. and the mixing time is 30 min;

[0104] (5) Molding: The mixed material is added to an extruder for plasticization, and then pressed into shape in a mold, and cooled to room temperature to obtain a degradable lunch box; the mold temperature is 135° C., the pressing pressure is 12 MPa, and the pressing time is 50 s.

[0105] Example 3

[0106] A production process for a degradable lunch box comprises the following steps:

[0107] (1) Preparation of materials: Weigh the following materials in parts by weight: 30 parts of bamboo powder, 75 parts of polylactic acid resin, 2 parts of stearate, 15 parts of composite modified filler, and 16 parts of starch.

[0108] The preparation method of the composite modified filler is as follows:

[0109] First, the bentonite is calcined to obtain calcined bentonite;

[0110] Add polybutylene succinate, calcined bentonite and coupling agent into a mixer in sequence, and mix and stir for 40 minutes to obtain a uniform mixture;

[0111] The uniform mixture obtained above is added into an internal mixer for internal mixing. After the internal mixing is completed, the mixture is discharged to obtain a composite modified filler.

[0112] The preparation method of calcined bentonite is:

[0113] The bentonite and nitric acid solution were mixed in a mass ratio of 1:5, heated to 80°C, stirred for 40 minutes, then centrifuged, filtered, washed to neutrality, and dried to obtain;

[0114] Wherein, the mass fraction of nitric acid solution is 5%;

[0115] The stirring speed is 300r / min;

[0116] The centrifugal speed was 8000 r / min and the centrifugal time was 15 min;

[0117] The drying temperature was 80°C and the drying time was 2 hours.

[0118] The mass ratio of polybutylene succinate, calcined bentonite and coupling agent is 12:25:1.4;

[0119] The coupling agent is an organic silane coupling agent;

[0120] The organic silane coupling agent is vinyltrimethoxysilane.

[0121] The mixing process parameters are:

[0122] The mixing temperature is 180°C, the mixing speed is 75r / min, and the mixing time is 40-50min.

[0123] The stearate is calcium stearate.

[0124] The starch is soybean starch;

[0125] The soybean starch is subjected to modification treatment:

[0126] The soybean starch is added to the nitric acid solution, the temperature is adjusted to 90°C, the mixture is kept warm and stirred for 2 hours, then adjusted to neutrality, and dried to a moisture content of less than 5% to obtain;

[0127] The mixing ratio of the soybean starch and the nitric acid solution is 30 g:120 mL.

[0128] (2) Mixing: Add each component to a high-speed mixer in sequence, mix the raw materials evenly, and obtain a mixed raw material; the mixing time in the high-speed mixer is 40 minutes;

[0129] (3) Internal mixing: the mixed raw materials are added into an internal mixer for internal mixing and kneading to obtain an internal mixing rubber material; the internal mixing temperature is 155°C and the time is 25 min.

[0130] (4) Mixing: adding the internal mixing rubber material to an open mixer for mixing to obtain a mixed material; the mixing temperature is 188° C. and the mixing time is 30 min;

[0131] (5) Molding: The mixed material is added to an extruder for plasticization, and then pressed into shape in a mold, and cooled to room temperature to obtain a degradable lunch box; the mold temperature is 135° C., the pressing pressure is 12 MPa, and the pressing time is 50 s.

[0132] Comparative Example 1:

[0133] On the basis of the technical solution of Example 1, the composite modified filler is replaced with an equal amount of bentonite, and the rest of the technical solutions remain unchanged.

[0134] Comparative Example 2:

[0135] Based on the technical solution of Example 1, soybean starch is replaced by corn starch, and the rest of the technical solutions remain unchanged.

[0136] Comparative Example 3:

[0137] Based on the technical solution of Example 1, the soybean starch is not modified, and the rest of the technical solutions remain unchanged.

[0138] test:

[0139] The samples of the embodiment were tested. The raw materials of the embodiment and the comparative example were made into the required test specimens in a standard mold at 170° C. using a flat vulcanizer and tested:

[0140] The notched impact strength test was carried out according to GB / T1843-2008, and the test was performed 5 times each, and the average value was taken:

[0141] Table 1

[0142] Impact strength J / m Example 1 885 Example 2 893 Example 3 862 Comparative Example 1 761 Comparative Example 2 825 Comparative Example 3 801

[0143] It can be seen from Table 1 that the degradable lunch box prepared by the present invention has higher impact resistance.

[0144] The tensile strength of the samples of the embodiment and the comparative example was tested according to GB / T1040.-2018, each test was performed 5 times, and the average value was taken:

[0145] Table 2

[0146]

[0147]

[0148] It can be seen from Table 2 that the degradable lunch box prepared by the present invention has excellent tensile properties.

[0149] Degradation performance test was performed on the embodiments and comparative examples:

[0150] Equal amounts of the samples of the embodiment and the comparative example were subjected to degradation test in 5 mL of 0.1 M Tris-HCl buffer, the concentration of proteinase K in the buffer was 0.15 mg / mL, and the degradation test was carried out in a vacuum oven at 50° C. After 60 hours, the samples were taken out, cleaned, dried, weighed, and the weight loss rate was calculated:

[0151] Table 3

[0152] Weight loss rate % Example 1 88.57 Example 2 89.03 Example 3 88.26 Comparative Example 1 82.79 Comparative Example 2 86.72 Comparative Example 3 85.08

[0153] It can be seen from Table 3 that the degradable lunch box prepared by the present invention has excellent degradability.

[0154] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A degradable lunch box, characterized in that: The invention comprises the following ingredients by weight: 20-30 parts of bamboo powder, 60-75 parts of polylactic acid resin, 1-2 parts of stearate, 10-15 parts of composite modified filler and 12-16 parts of starch.

2. A degradable lunch box according to claim 1, characterized in that: The preparation method of the composite modified filler is: First, the bentonite is calcined to obtain calcined bentonite; Add polybutylene succinate, calcined bentonite and coupling agent into a mixer in sequence, and mix and stir for 40 minutes to obtain a uniform mixture; The uniform mixture obtained above is added into an internal mixer for internal mixing. After the internal mixing is completed, the mixture is discharged to obtain a composite modified filler.

3. A degradable lunch box according to claim 2, characterized in that: The calcined bentonite preparation method is: The bentonite and nitric acid solution were mixed in a mass ratio of 1:5, heated to 80°C, stirred for 40 minutes, then centrifuged, filtered, washed to neutrality, and dried to obtain; Wherein, the mass fraction of nitric acid solution is 5%; The stirring speed is 300r / min; The centrifugal speed was 8000 r / min and the centrifugal time was 15 min; The drying temperature was 80°C and the drying time was 2 hours.

4. A degradable lunch box according to claim 2, characterized in that: The mass ratio of the polybutylene succinate, calcined bentonite and coupling agent is 10-12:20-25:1-1.4; The coupling agent is an organic silane coupling agent; The organic silane coupling agent is vinyltrimethoxysilane.

5. The degradable lunch box according to claim 2, characterized in that: The mixing process parameters are: The mixing temperature is 180°C, the mixing speed is 75r / min, and the mixing time is 40-50min.

6. The degradable lunch box according to claim 1, characterized in that: The stearate is calcium stearate.

7. The degradable lunch box according to claim 1, characterized in that: The starch is soybean starch; The soybean starch is subjected to modification treatment: The soybean starch is added to the nitric acid solution, the temperature is adjusted to 90°C, the mixture is kept warm and stirred for 2 hours, then adjusted to neutrality, and dried to a moisture content of less than 5% to obtain; The mixing ratio of the soybean starch and the nitric acid solution is 30 g:120 mL.

8. A production process for a degradable lunch box according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Preparation of materials: weighing bamboo powder, polylactic acid resin, stearate, composite modified filler, and starch according to respective weight parts; (2) Mixing: Add each component to a high-speed mixer in sequence, mix the raw materials evenly, and obtain a mixed raw material; (3) Banburying: Adding the mixed raw materials to a banbury mixer for banburying and kneading to obtain a banburying rubber compound; (4) Mixing: adding the mixed rubber material to an open mixer for mixing to obtain a mixed material; (5) Molding: The mixed material is added to an extruder for plasticization, and then pressed into shape in a mold, and cooled to room temperature to obtain a degradable lunch box.

9. The production process of a degradable lunch box according to claim 8, characterized in that: The mixing time in the high-speed mixer in step (2) is 40 minutes; The temperature of the banburying in step (3) is 155° C. and the time is 25 min.

10. The production process of a degradable lunch box according to claim 8, characterized in that: The mixing temperature in step (4) is 188° C. and the mixing time is 30 min; In step (5), the mold temperature is 135° C., the pressing pressure is 12 MPa, and the pressing time is 50 s.

Citation Information

Patent Citations

  • Nanometer bentonite composite flame-retardant polylactic acid bioplastics and preparation method thereof

    CN102838859A

  • Bentonite / starch composite degrading material produced by melt intercalation and preparation method

    CN104497365A

  • Antibacterial degradable packing box and preparation method thereof

    CN107805377A

  • Bamboo powder full biodegradable material and preparation method thereof

    CN110343397A

  • High-density bamboo powder modified polylactic acid biodegradable plastic and preparation method thereof

    CN111500037A